(untitled) (Comprehensive Journal of Science, 2025)
Feryal Amohamed Mohamed Abu Zubaydah University of Tripoli – Faculty of Arts Department of History and Archaeology – Medieval Studies Division This study aims to analyze the concept of authority and methods of governance in the Umayyad era through two prominent experiences: the experience of Muʿāwiya ibn Abī Sufyān, who established a new model that combined the caliphate with kingship, and the experience of ʿAbd al-Malik ibn Marwān, who consolidated this model by re-centralizing authority and concentrating it in the hands of the caliph. The importance of this study lies in its focus on the historical transformation witnessed by the Islamic state in the first century AH, as it shifted from the model of the Rashidun Caliphate—based on religious legitimacy and consultation—to the Umayyad model of kingship, founded on tribal solidarity and centralized power. The study adopts an analytical comparative approach, examining the manifestations of authority and methods of governance during the reigns of both Muʿāwiya and ʿAbd al-Malik, highlighting the similarities and differences between them, thereby offering a deeper understanding of the nature of authority in this pivotal stage of Islamic history.